Some problems on science-technology strategies - Long, Hoang Xuan; Chi, Hoang Lan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
We are entering to the time for conclusion evaluations of science-technology strategies of 2011-2020 period and the building of science-technology strategies for 2021-2030 period. The conclusion evaluations of strategies, also important as the building of strategies, are complex works. Here the paper provides contributions to view some concepts on science-technology strategies. This paper is to clarify some aspects on S&T strategies on leap forward development and scientific natures in documents of science-technology strategies, definition of objectives of science-technology strategies only on basis of old indicators, statistic works and objectives of science-technology strategies, science-technology strategies of businesses and national science-technology strategies, and innovation in science-technology strategies. At the same time, the paper indicates that the unproper concepts on science-technology strategies would lead to numerous consequenses. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;"> Code: 20011001